Prospective assessment of short-term propylene glycol tolerance in neonates. Issue 12 (19th October 2010) - Allegaert, Karel; Vanhaesebrouck, Sophie; Kulo, Aida; Cosaert, Katrien; Verbesselt, Rene; Debeer, Anne; de Hoon, Jan
Abstract : Introduction: Propylene glycol (PG) is an unintentional frequently administered solvent in neonates despite the fact that PG accumulation potentially results in hyperosmolarity, lactic acidosis and renal/hepatic toxicity. Methods: Prospective evaluation of renal (diuresis, creatinaemia, sodium), metabolic (base excess, anion gap, lactate, bicarbonate) and hepatic (alanine transaminase, aspartate aminotransferase, direct bilirubinaemia) tolerance to PG in (pre)term neonates following intravenous administration of formulations (paracetamol, phenobarbital, digoxin) that contain PG. Observations from 48 h before up to 48 after the last PG administration were described and compared (paired analysis). Clinical characteristics and observations collected following intravenous PG-paracetamol administration were compared with a historical cohort of neonates in whom similar (renal, hepatic) observations during exposure to a mannitol-containing paracetamol formulation were collected. Results: 5566 observations were collected in 69 neonates before, during and following median PG exposure of 34 mg/kg/24 h (range 14–252). Progressive postnatal adaptation in renal, metabolic and hepatic function was documented, unrelated to the PG exposure. In the subgroup of 40 cases treated with intravenous PG-paracetamol, observations on renal and hepatic function were similar to a historical cohort of published observations following exposure to intravenous mannitol-paracetamol. Conclusions: Unintended PG administration (34 mg/kg/24 h) for a maximum of 48 h seems to be tolerated in (pre)term neonates and does not affect short-term postnatal adaptations. Further studies on PG disposition and the level of safe exposure to PG, including long-term safety data in neonates are needed.